User-Centered Design for a Multi-Role Academic Support System in Higher Education - Fonita Theresia Yoliando; Wella; Ririn Ikana Desiyanti (de-lite, 2025)
Effective academic support is a critical component of student success in higher education. As institutions increasingly adopt student-centered learning models, academic counseling emerges as a key mechanism to provide guidance and address individual learning needs. Despite its importance, the counseling process often suffers from structural limitations. Lecturers face heavy workloads that constrain their ability to offer personalized support, while counseling records are typically fragmented and difficult to track. This study aims to design and develop a multi-user system to streamline academic advising and student progress monitoring. The platform incorporates four essential functions: academic scheduling, counseling engagement, performance tracking, and study plan records. It is intended to serve a range of users, including students, faculty advisors, academic staff, and institutional leaders, by facilitating timely and data-informed decision-making. To ensure the system aligns with user needs, a User-Centered Design (UCD) methodology was applied. Focus group discussions were conducted with stakeholders across various roles, including students, lecturers, program heads, deans, and academic staff. The insights were translated into functional requirements, flowcharts, information architecture, and user interface design. The paper also discusses the iterative design process, highlights challenges encountered during development, and offers recommendations for institutions seeking to implement integrated academic support systems.